Influencer Culture and Public Opinion: A Study on the Impact of Digital Influencers on Political Mobilization - Meilinda, Vivi; Fransisca, Vika (Islamic Journal of Communication and Public Discourse, 2024)
This study aims to analyze the influence of influencer culture on public opinion and political mobilization in Indonesia. Using descriptive quantitative methods and purposive sampling approaches, data was collected from 400 respondents of active social media users who followed digital influencers who voiced political views. The results of the analysis show that digital influencers have a significant influence in shaping political views and mobilizing political action among their followers, especially the younger generation. These findings reveal that trust in influencers plays an important role in amplifying the effects of this influence. Based on agenda-setting theory, influencers act as agents who are able to direct public attention to certain issues, strengthen political participation, but also have the potential to pose challenges related to the accuracy and objectivity of information. Therefore, this study highlights the importance of digital literacy and regulatory settings to prevent the potential manipulation of political information through social media.